Computer algorithm for comparing and ordering models based on indicators and user value - Aliaga-Benavides, Adriel Alejandro; Santana-Pacheco, Yudisel; Mustelier-Hechavarría, Antonio; Guzmán-Bazán, Yuniel (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Sometimes a list of models can be compared using a set of indicators, ordered by the user’s criterion, given that it is known whether the growth of the indicators value affect the user’s interests. This paper proposes a computational algorithm that compares models, assigning them a numerical value that corresponds to the priority given to each model indicator by the user. The proposed algorithm allows to rank the models as other known algorithms do, such as the vector space model; however, it takes into account user comparison priorities. When working with lineal functions, the margin of error in the algorithm calculations is null. The algorithm is validated by the software Ambiens v1.0, whose purpose is to manage the waste control information, showing relevant results in the comparison of models. The algorithm essence is the need to identify the best model of the group, according to the user’s criterion per indicator.